Ethnocultural Specific of Idioms: From Traditional to Innovative Paradigms - Alefirenko, Nikolai F.; Lagodenko, Julietta V.; Chumak-Zhun, Irina I.; Goleva, Natalya M.; Zhilenkova, Irina I. (Journal of History Culture and Art Research, 2018)
The ethno-cultural aura of phraseology is revealed in conjunction with the comprehension of the secrets of the linguistic mentality of peoples that generates the idiomatics of native languages. Since traditionally ethno-cultural specificity of phraseology was studied at the level of a country study description, an attempt was made to elucidate the work of cognitive-pragmatic mechanisms for the formation of phraseological imagery. The first method is aimed at revealing the ethno-cultural component in the value-semantic potential of phraseme building components, called culturally significant realia. However, the authors do not confine themselves to this method, which narrows the reference of phraseme building components. An integrated approach to the identification and description of the ethno-cultural component is proposed, using the analysis of the integrated configuration of the four factors of the formation of the axiological content of phrasemes.